“A descriptive study of the options to do the community work of 5 in the Communication Specialization area from the Bachelor of Arts in Modern Languages in Semester I/2019” - Cuchilla de De León, Nataly Alejandra; Palacios Machuca, Verónica Elizabeth; Villanueva Henríquez, Flor de María (2024)
The study was based on knowing and making a descriptive study of the options to do the community work of fifth-year students in the communication area from the Bachelor of Arts in modern Languages in semester I/2019 focusing on implementation of community work when they choose the communication specialization. The population of the study was based on the fifth-year students who developed their community work in Bachelor of Arts in Modern Languages with specialization in French and English. The practitioners wanted to identify some of the problems and the level of satisfaction or in satisfaction they faced in the process. Besides, an interview was conducted to the students in order to get more specific information that helped and facilitated to practitioners to gather deeper information about the research topic. The method applied in this research was the mixed method (qualitative and quantitative approaches). The outcome of the study indicated the feeling and experiences obtained in the students during the process of their community work. In order to implement a previous and good orientation for the students of the Bachelor of Arts in Modern Languages Specialty in English and French at the beginning of the major that one may provide guiding to the students when choosing one of the two specializations.